What's next after metformin? focus on sulphonylurea: add-on or combination therapy - Lim PC; Chong CP (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Introduction: The pathophysiology of type 2 diabetes (T2DM) mainly focused on insulin resistance and insulin deficiency over the past decades. Currently, the pathophysiologies expanded to ominous octet and guidelines were updated with newer generation of antidiabetic drug classes. However, many patients had yet to achieve their target glycaemic control. Although all the guidelines suggested metformin as first line, there was no definite consensus on the second line drug agents as variety of drug classes were recommended. Objectives: The aim of this review was to evaluate the drug class after metformin especially sulphonylurea and issues around add-on or fixed dose combination therapy. Methods: Extensive literature search for English language articles, clinical practice guidelines and references was performed using electronic databases. Results: Adding sulphonylurea to metformin targeted both insulin resistance and insulin deficiency. Sulphonylurea was efficacious and cheaper than thiazolidinedione, dipeptidyl peptidase-4 inhibitor, glucagon-like peptide 1 analogue and insulin. The main side effect of sulphonylurea was hypoglycaemia but there was no effect on the body weight when combining with metformin. Fixed dose sulphonylurea/metformin was more efficacious at lower dose and reported to have fewer side effects with better adherence. Furthermore, fixed dose combination was cheaper than add-on therapy. In conclusion, sulphonylurea was feasible as the second line agent after metformin as the combination targeted on two pathways, efficacious, cost-effective and had long safety history. Fixed dose combination tablet could improve patient's adherence and offered an inexpensive and more efficacious option regardless of original or generic product as compared to add-on therapy.